জীবনানন্দ দাস দিনলিপি : লিটারারি নোটস ৩ (জুলাই ১৯২৫/এপ্রিল ১৯২৯-মার্চ ১৯৩০) - গুহ, ভূমেন্দ্র; মিএ, গৌতম
critical articles on literary notes of Jibanananda Das, 1899-1954, 20th century Bengali poet; includes text of notes and biographical information.